Analysis of influencing factors in chronic kidney disease incidence in Indonesia - Meilinah Hidayat; Fabiola Motulo; Santoso Chandra; Stephanie Andamari; Janto Sulungbudi; Ronny Lesmana (Faculty of Medicine, Universitas Islam Indonesia, 2023)
Background: The incidence of chronic kidney disease (CKD) continues to increase from year to year. There was an increase in CKD rates in the 2013 and 2018 basic health research or Riset kesehatan dasar (Riskesdas). Several provinces in Indonesia show a high incidence of CKD and require hemodialysis. As the incidence of CKD increases, it is important to investigate the influencing factors.Objective: To identify the influencing factors of CKD incidence in Indonesia.Methods: Data from 11 provinces with the highest incidence of CKD and hemodialysis were obtained from the Indonesian Ministry of Health through the Riskesdas 2018 survey. For comparison, the incidence of hemodialysis patients in 2020 at Immanuel Hospital Bandung was included in the investigation. All data were analysed using a Python software program, and a decision tree was determined. The results of the decision tree were analysed using Chi-square. Subject profiles were descriptively analysed for some Riskesdas 2018 data and medical records at Immanuel Hospital. Results: The total data from Riskesdas was 130,787 subjects, among those, there were 610 people with CKD/hemodialysis, meanwhile data of 79 people with hemodialysis were obtained from Immanuel Hospital. The odds ratios of diabetes mellitus was 4.54 (p=0.000), hypertension was 3.00 (p=0.000), salty food was 2.26 (p=0.000), waist circumference (WC) was 1.35 (p=0.025), and body mass index (BMI) was 1.06 (p=0.605). Conclusion: Diabetes, hypertension, salty foods, WC and BMI are the five most important factors influencing the incidence of CKD in Indonesia. These variables need to be managed properly to reduce the incidence of CKD.